HOST ROCKS’ GEOCHEMISTRY AND MINERALIZATION POTENTIAL OF POLYMETALLIC EPITHERMAL QUARTZ VEINS AT SORIPESA PROSPECT AREA, SUMBAWA ISLAND, INDONESIA - Win Khant; I Wayan Warmada; Arifudin Idrus; Lucas Donny Setijadji; Koichiro Watanabe (Geological Engineering Department Universitas Gadjah Mada, 2015)
The Soripesa prospect area is located at Maria village, Wawo district, Bima region in the eastern part of Sumbawa Island, Indonesia. This area is a part of Cenozoic Calc-alkaline volcanic inner Banda- Sunda Arc. There are five main polymetallic epithermal quartz veins in the Soripesa prospect area, namely, Rini vein, Jambu air vein, Dollah vein,Merpati vein, and Arif vein. The dominant lithology is a lithic-crystal tuff of andesitic and dacitic composition and bedded limestone. Major oxides and trace elements were analyzed by using X-Ray Fluorescence (XRF) to identify the host rock geochemistry. The main veins are hosted by andesitic and andesitic/ basaltic volcanic host rocks. Major elements compositions are affected by alteration. Based on the trace element data, host rocks of all veins were formed in the volcanic arc basalt (VAB) and island arc basalt (IAB) tectonic settings. Host rocks of Rini vein contain higher amount of precious and base metal elements (Zn, Cu, Pb, and Ag.etc.) than those of other host rocks. Keywords: Soripesa prospect area, lithology, tectonic setting, mineralization.